Intraventricular Neurilemmoma (Schwannoma): Shall GFAP Immunostaining Be Regarded as a Histogenetical Tag or as a Mere Histomimetical Trait? - Miguel Fdo. Salazar; Martha Lilia Tena Suck; Daniel Rembao Bojórquez; Citlaltepetl Salinas Lara (Case Reports in Pathology)
Neurilemmomas are benign neoplasms presumedly derived from Schwann cells which rarely originate within the central nervous system. Moreover, their intraventricular location has been seldom noticed with less than 30 cases reported worldwide. Here, we add another case study to the record as well as the fifth one in Latin American population. A 16-year-old boy without significant past clinical data debuted with headache and progressive left eye blindness during six months. Neuroimaging scans showed a bulky, multiloculated, intraventricular tumour emerging from the posterior horn of the left lateral ventricle. Microscopically, the lesion put on view the classical schwannian histology: spindle cells arranged in both compact and loosely textured areas. Verocay bodies were not present but vessel hyalinisation, pericellular reticulin, and senescent atypia were observed. The immunoperoxidase reactions were also consistent with neurilemmal differentiation; however, glial fibrillary acidic protein expression was widespread and unexpectedly seen. Traditionally conceived as “nerve sheath tumours” the dual immunophenotype herein demonstrated points to a different histogenetical pathway other than sheer Schwann cell derivation. As previously advised by some authors, neoplastic transformation from a multipotent stem cell may explain the occasional finding of these tumours in unconventional intracranial compartments.